COPD patients with peripheral airway obstruction reversibility identified by exhaled nitric oxide. (1st April 2019) - Pérez-Bogerd, Silvia; Michils, Alain; Malinovschi, Andrei; Van Muylem, Alain
Abstract: Rationale: Besides its role as an inflammatory marker in asthma, fractional exhaled nitric oxide (FE NO) provides information on the extent of the airway obstruction process through evaluating its change after bronchodilation. Objective: To investigate whether FE NO change after bronchodilation can identify different sites of airway obstruction in COPD patients. Methods: FE NO, FEV1 and the slopes (S) of the alveolar plateau of the single breath washout test (SBWT) were measured in 61 stable COPD patients (FEV1 34.5% predicted) before and after the inhalation of 400 μ g salbutamol. SBWT used Helium (He), and sulfur-hexafluoride (SF6 ). Obstruction relief occurring in pre-acinar and intra-acinar small airways is expected to decrease SHe and SSF6, respectively. Indices changes (Δ) after bronchodilation were expressed as a percentage of pre-bronchodilation values. Results: FE NO stability (∣ΔFE NO∣ ≤ 11%) was observed in 19 patients [−2.7(6.7)%] [mean (SD)] (NO = group); ΔFE NO > 11% [+37.4(27.7)%] in 20 patients (NO+ group) and ΔFE NO < −11% in 22 patients [−31.2(9.8)%] (NO− group). A similar ΔFEV1 ( p  = 0.583; [+9.4(9.6)%]) was found in the three groups. In NO = and NO+ groups, neither SHe nor SSF6 changed; in NO− both SHe [−12.4(27.5)%, p  = 0.007] and SSF6 [−20.2(20.4)%, p  < 0.001] significantly decreased. Conclusion: Different patterns of FE NO response to β 2 -agonists were observed in COPD most likely depending on the extent of the dilation process. A profile of airway obstruction with an extensive β 2 -agonist response down to lung periphery is identified by FE NO reduction after acute bronchodilation in 30% of COPD patients. The clinical relevance of this profile requires further investigation.